Surgical management of testicular torsion - Gajbhiye, Ashok Suryabhanji; Shamkuwar, Ambrish; Surana, Kuntal; Jivghale, Kishor; Soni, Mahesh Kumar (International Surgery Journal, 2016)
Background: Testicular torsion is a correctable true surgical emergency and early diagnosis forms the basis for salvaging this catastrophe. Hence the aim of this study is to identify factors and discuss the management of torsion of testes. Methods: A prospective study was carried out from 2005 to 2015 at our institute and total 60 cases diagnosed as testicular torsion were studied. The clinical features, radiological investigations and treatment measures were evaluated in details. Results: Of total 60 cases of testicular torsion the mean age of presentation was 20±5.5 years. The patients presented 12 hours after onset of pain. Pain was present in all 60 (100%) patients. Left testes involved in 38 (63.33%) patients and right in 22 (36.67%) patients. With only the facilities of ultrasound it was found that it was useful in 56 (93.33%) patients. All patients were explored and only 12 (20%) patients had a successful detorsion while 48 (80%) cases underwent orchidectomy. No post-operative complications were noted. Conclusions: According to our results nearly 80% cases presented late and hence testes could not be salvaged. Left testicular torsion is more common in our region and ultrasonography is a reliable diagnostic tool. Proper awareness, health education and prompt surgical intervention, forms the key to prevent removal of an organ which signifies masculinity.